Survey Tendangan Lurus Di Bawah Pinggang Dalam Olahraga Bela Diri Tarung Derajat Satlat Diklat Kota Kupang - Tampani, Agri Rivin; M. Boleng, Lukas; Dwi A. Fufu, Ronald (Nusa Cendana University, 2024)
This research will be carried out at the Education and Training Satlat on Jl. Fektor Funay Kolhua, Maulafa District, Kupang City. The researcher chose this location for the reason that in the Maulafa District Education and Training Satlat, Kupang City, there are informants who can help the researcher to collect data from the Influence of Straight Kicks in Martial Arts Combat Sports. The ability to kick straight is one of the kick techniques that also determines success to achieve maximum achievement in pencak silat sports. According to Sajoto (1988), it is stated that to achieve good achievements in sports, it is necessary to have elements of biomotor abilities such as speed, strength, endurance, power, precision, flexibility, and balance. In learning or practicing kicking, many exercises are neede d. This type of research is a type of qualitative research. What is meant by qualitative research is to find out the situation or condition of an area being studied. Mukhtar (2013: 10) stated that descriptive research is a research that is intended to collect information about the subject of this research, the researcher uses qualitative descriptive. According to Moleong (2017: 6), qualitative research is research that intends to understand the phenomenon of what is experienced by the object of research such as behavior, perception, motivation, action and others holistically and by means of descriptions in the form of words and language, in a special natural context.